Pelatihan Pembuatan Media Big Book Bagi Guru PAUD/TK di Kota Bandar Lampung Tahun 2021 - Asih Budi Kurniawati; Devi Nawangsasi; Nopiana (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2022)
Interest in reading can be increased through interesting learning for children by learning through play. This play activity can arouse children's interest and interest in reading. For this reason, adequate competence is needed for teachers to be able to arouse the interest and interest of the child. This service activity is intended to provide training in making big book media for PAUD teachers in Bandar Lampung City as well as to see how the efforts of teachers in making big book media for early childhood are varied. The method used in this activity is the informative – participatory method, which requires the participants to have theoretical and practical insights about making big book media for PAUD teachers through stages of activities that include information presentation, discussion and simulation. The technique used in delivering the training material is a workshop using multimedia aids in the form of a laptop, LCD, teaching aids, post test and pretest. After the implementation of the training on making big book media, there was a significant increase in teacher knowledge. It was proven that the teacher was able to answer all the post-test questions correctly. Therefore, it is hoped that teachers can use this knowledge to optimize and implement it in learning.